Microsoft Producer 2003 - Shelly, Gary B. (Cengage Learning, Inc, 2005)
This text introduces students to Microsoft Producer for PowerPoint2003, the ideal tool for creating engaging presentations, training, and business communications. The title includes material to accompany a course that teaches PowerPoint 2003 as the primary component, or a course that teaches other applications or computer concepts